2012
DOI: 10.3329/cardio.v5i1.12276
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Sensitivity Pattern of Bacterial Isolates from Different Clinical Specimens: Experience at NICVD, Dhaka

Abstract: Background: Infectious diseases are among the leading causes of death and sometimes curable.  Bacteria are the most common etiology in hospitalized patients. The objective of this study was to  evaluate the incidence of bacterial infections and their pattern of susceptibility to antibiotics in  moderate and severe infections in patients admitted at NICVD hospital.Methodology: The study was performed in the apical teaching hospital of Bangladesh situated at  Dhaka in the first half of 2012. Patients admitted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In this study the highest prevalence of bacteria was isolated from urine followed by sputum, blood and wound infections. More or less a similar result was reported by MS Shahidullah et al 15 Negative outcome of inadequate and inappropriate antimicrobial treatment of infections caused by antibioticresistant bacteria has been shown in previously published studies. 1619 Hence it is suggested that the physicians need to reevaluate initial therapies to ensure appropriate antibiotic cov erage.…”
Section: Discussionsupporting
confidence: 73%
“…In this study the highest prevalence of bacteria was isolated from urine followed by sputum, blood and wound infections. More or less a similar result was reported by MS Shahidullah et al 15 Negative outcome of inadequate and inappropriate antimicrobial treatment of infections caused by antibioticresistant bacteria has been shown in previously published studies. 1619 Hence it is suggested that the physicians need to reevaluate initial therapies to ensure appropriate antibiotic cov erage.…”
Section: Discussionsupporting
confidence: 73%
“…Infection was considered when there was serous discharge from stitches, wound dehiscence, high temperature at temperature chart at ICU and wards, evidence of secondary suturing, sternal restabilization, antiseptic dressing, report of culture sensitivity of pus with positive infective micro-organisms and list of antibiotics sensitive or resistant to it, or any mortality due to infection in ICU and wards; or any evidence of renal impairment and other adverse effect such as 'red man syndrome'. 26 These findings were similar to this study . Teicoplanin was used to prevent sternal infection as Tecoplanin penetrates in to the bony tissue very well.…”
Section: Antibiotic Regimesupporting
confidence: 83%
“…11 It is particularly true for developing countries like Bangladesh where antibiotics are prescribed irrationally not only by the medical practitioners but the antibiotics are also purchased directly from the chemists like medicine shop keepers without prescription. 7 Palikhe reported similar reason. 12 It has been advised that clinicians should be aware of the rising resistance of bacteria to commonly prescribed antibiotics as well as the profile of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 54%
“…17 Nasal carriage of S. aureus is an important risk factor for infection of surgical site as the organism is a normal flora in the nostrils. 7 Again, it is found that with the disruption of natural skin barrier Staphylococcus aureus, which is a common bacterium on surfaces of the body, can easily find the way into breach of the skin surfaces. The high prevalence of Pseudomonas infection may be because it is an exogenous source of infection and it is assumed that infection with this organism may also be due to contamination from the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation